Polemik Nasakh dalam Kajian Ilmu Al-Qur’an - Fawaid, Ahmad (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
This article explores an important discipline in QurÃ¢â‚¬â„¢anic sciences, namely nasikh-mansukhÃ‚Â (the abrogator and the abrogated), referring to the abrogation of certain QurÃ¢â‚¬â„¢anic verses.Ã‚Â Although Muslim scholars are in dispute over the exact meaning and implications of the meaning of abrogationÃ‚Â (naskh)Ã‚Â in the QurÃ¢â‚¬â„¢an, nevertheless there are some points of agreement.Ã‚Â Neither ide either completely rejects the concept of abrogation, or vice versa, and their differences are not non-negotiable.Ã‚Â In some cases, the two sides will arrive at the same conclusionÃ‚Â in that they will both admit the existence of the concept ofÃ‚Â naskh (abrogation) in the QurÃ¢â‚¬â„¢an, but will disagree on its meaning. One side will interpret naskh as complete cancellation and erasure, while the other side tends to interpret it as implying a delay in the implementation (or rather, evolution) of Islamic law (shariÃ¢â‚¬Ëœah). Thus one side admits of intra-Qur'anic abrogation, while the other only admits of abrogation in extra-Qur'anic contexts.